The financial policy of Islam and its status and role among the existing financial policies - ياسين صالح عبد الكريم; شەوبۆ عثمان بكر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Islam has declared a different system for living and it has pointed out what do humanity need for a happy and comfortable life, one of these important systems that Islamic law has concerned about the prophet and his companions has applied is the economic system and more specifically fiscal policy they gave a real attention to it, and said successful loans and durable policy for fiscal policy that has overcame most of other policies that had been sat by other economic systems by which Islamic state has endured It’s financial problems during its first days it removes classes from society abusing cheating stealing the faults money Pura and Idleness. That is why if the world of lies this policy then the birds will return to their flocks and jobs to the pros specially after the failure of the current policy this research tries to explain. And simplify the fiscal policy in Islam and it’s position in today’s world.